2013
DOI: 10.1016/j.jcin.2013.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk Score, Causes, and Clinical Impact of Failure of Transradial Approach for Percutaneous Coronary Interventions

Abstract: In a high-volume radial center, 2.7% of patients undergoing PCI are excluded from initial TRA on clinical grounds, whereas crossover to femoral approach is required in only 1.8% of the cases. A new simple clinical risk score is developed to predict TRA-PCI failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 26 publications
4
65
0
3
Order By: Relevance
“…The feasibility of PCI by radial access is clearly lower than the 90% recently described in a 'real-life' population of uncomplicated ST-elevation MI [18]. Indeed, CS is a strong independent predictor of transradial approach PCI failure [19]. Nevertheless, the rate of radial access in our study remained high, considering the critical basal status of our population, underlined by the high proportion of patients requiring inotropic drugs -nearly sixfold higher than the rate reported by Mamas et al [16].…”
Section: Discussionmentioning
confidence: 80%
“…The feasibility of PCI by radial access is clearly lower than the 90% recently described in a 'real-life' population of uncomplicated ST-elevation MI [18]. Indeed, CS is a strong independent predictor of transradial approach PCI failure [19]. Nevertheless, the rate of radial access in our study remained high, considering the critical basal status of our population, underlined by the high proportion of patients requiring inotropic drugs -nearly sixfold higher than the rate reported by Mamas et al [16].…”
Section: Discussionmentioning
confidence: 80%
“…Previous work has suggested that patients undergoing femoral procedures in predominantly radial centers tend to be older, more hemodynamically unstable, and have a greater prevalence of adverse procedural risk factors, such as renal failure, poor left ventricular function, and at higher bleeding risk 12,13,31 as defined by the Mehran bleeding risk score. 32 Our work shows that nearly 60% of centers in the United Kingdom (53 of 92 centers) have transitioned to become predominantly radial centers with more than two-third of their PCI case mix being undertaken through the TRA approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies demonstrated that the risk of access failure and need for crossover was higher with TRA versus TFA (7.3% vs 2%, p<0.01),11 recent registries have shown relatively lower need for crossover with improved materials and technical expertise 18 19 27. Crossover from TRA to TFA in primary PCI for STEMI in recent studies has been reported to range from 3.7% to 9.6% 13 14 28 29.…”
Section: Discussionmentioning
confidence: 99%